The Effect of Financial Literacy and Locus of Control towards Financial Management behavior among Gen Z as Online Lenders - Restiyanti, Wening; Yadiati, Winwin (Journal of Accounting Auditing and Business, 2024)
It has been observed that online loans are widely used in Indonesia among people of productive age, but there are concerns about their knowledge and self-control, which can affect their financial management behavior. To address this, a study was conducted to examine the impact of financial literacy and locus of control on the financial management behavior of Generation Z individuals (aged 18 to 28 years) who use or have used the ShopeePinjam and/or ShopeePayLater platforms. The data was gathered from 202 respondents through online social media platforms. The findings of the study show that financial literacy and locus of control have a significant impact on financial management behavior, both partially and simultaneously. Although the respondents had a high level of financial literacy and locus of control, they lacked an understanding of risk and return, the concept of time value of money, and confidence in their abilities to enhance their well-being. While the overall value of the dependent variable was high, a few instruments had a relatively low percentage.